Exploring the relationships between transformational leadership, teachers' empowerment and school effectiveness in Malaysian primary schools - Maniam, Indra Devi; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The purpose of this paper is to develop a conceptual model in exploring the relationship between transformational leadership, teachers' empowerment and school effectiveness in Malaysian primary schools. This conceptual paper were develop based on three theories; Transformational Leadership Theory, Empowerment Theory and School Effectiveness Theory. Based on extensive literature review, seven dimensions of transformational leadership (Avolio and Bass, 1992), six factors of teachers’ empowerment (Short and Rinehart, 1992) and eleven dimensions of school effectiveness (Mortimore, 1995) are identified to construct the model.